Multimodal prehabilitation program for patients undergoing elective surgery for colorectal cancer: a scoping review - Gao, Shilin; He, Yuhua; Jiang, Lili; Yang, Jie (Frontiers in Oncology, 2025)
ObjectivesMultimodal prehabilitation has been widely used in patients undergoing surgery for colorectal cancer and has improved clinical outcomes. The aim of this scoping review is to review the content and current state of clinical practice of multimodal prehabilitation programs.MethodsA systematic literature review of multimodal prehabilitation studies in patients undergoing colorectal cancer surgery was conducted according to the PRISMA extension framework for scoping reviews. The literature was searched via the PubMed, Web of Science, SCOPUS, EMBASE and Cochrane Library databases. The results of the study included the components of multimodal prehabilitation (exercise, nutritional, and psychological interventions) and related evaluation indicators, duration, and compliance-related components.ResultsThis review included 12 studies with 9 randomized controlled trials, 1 pilot intervention study, 1 cohort study, and 1 mock-target trial design. Specific protocols for multimodal rehabilitation training vary widely, ranging in duration from 2–8 weeks, and were implemented in healthcare facilities, the community, and at home. Adherence rates ranged from 50% to almost 100%. Common outcome indicators include the 6-minute walk test, comorbidities, length of hospitalization, health-related quality of life, and several anxiety assessment scales.ConclusionCurrent evidence suggests that multimodal preconditioning has a positive effect on the clinical prognosis of patients undergoing elective colorectal cancer surgery. However, owing to the heterogeneity of multimodal rehabilitation in terms of implementation protocols and evaluation metrics, many high-quality studies are still needed to explore the optimal model of multimodal rehabilitation and promote its standardization.